Care – A Map of Contemporary Discussions and Pedagogical Challenges - Kopciewicz, Lucyna; Ferenc, Klaudia (INSTED: Interdisciplinary Studies in Education & Society, 2024)
The aim of the article is to reflect on care as a theoretical category in pedagogy, the ethical dimension of emotional work inscribed in care relations and the binder of social bonds. The authors review the idea of care in the theories of universalist ethics of principles, in ethology and animal psychology, in gender, post-humanist and non-anthropocentric contexts. The overview of selected concepts of care proves the high complexity of this concept and its diverse, ambivalent meanings. Care is related to reflection on the world, culture, and society - it accompanies reflection on weakness and fragility, inherent in the existence of not only what is human.